2022
DOI: 10.3390/jox12010004
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin for Treating Psychiatric Disorders: A Psychonaut Legend or a Promising Therapeutic Perspective?

Abstract: Psychedelics extracted from plants have been used in religious, spiritual, and mystic practices for millennia. In 1957, Dr. Hofmann identified and synthesized the prodrug psilocybin, a substance present in more than 200 species of psychedelic mushrooms. Although there were limitations related to the scientific design of many studies, clinical observations performed during the 1950s and 1960s showed a potential therapeutic effect of psilocybin for patients affected by depressive symptoms, anxiety, and conversio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Psilocybin has a high affinity for the serotonin receptor 5-HT 2A , and milder affinity for serotonin receptors 5-HT 1A and 5-HT 2C , as well as other serotonin and non-serotonin receptors. 44 , 73 , 74 While pretreatment with ketanserin, a 5-HT 2A antagonist, can block the psychomimetic effects of psilocybin, 75 one animal study found that ketanserin did not appear to block its antidepressant action. 74 In addition, stimulation of both the 5-HT 1A and 5-HT 2A receptors could be linked to striatal dopamine release, suggesting that psilocybin-induced psychotropic effects could be both dopaminergic and serotonergic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psilocybin has a high affinity for the serotonin receptor 5-HT 2A , and milder affinity for serotonin receptors 5-HT 1A and 5-HT 2C , as well as other serotonin and non-serotonin receptors. 44 , 73 , 74 While pretreatment with ketanserin, a 5-HT 2A antagonist, can block the psychomimetic effects of psilocybin, 75 one animal study found that ketanserin did not appear to block its antidepressant action. 74 In addition, stimulation of both the 5-HT 1A and 5-HT 2A receptors could be linked to striatal dopamine release, suggesting that psilocybin-induced psychotropic effects could be both dopaminergic and serotonergic.…”
Section: Discussionmentioning
confidence: 99%
“… 74 In addition, stimulation of both the 5-HT 1A and 5-HT 2A receptors could be linked to striatal dopamine release, suggesting that psilocybin-induced psychotropic effects could be both dopaminergic and serotonergic. 73 , 76 …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that psychedelic mushrooms were used for entheogenic and medicinal purposes across Mesoamerica from the early 16th century (Van Court et al, 2022). From the 1960s, psychedelics were extensively used as recreational drugs and by the early 1970s, global repressive policies and laws largely stifled research in this field (Coppola et al, 2022). Over the past decade, there has been a resurgence of research into the therapeutic applications of psychedelics, particularly in psychiatry (Nutt and Carhart-Harris, 2021;Phelps et al, 2022).…”
Section: Psychedelics and Neuroplasticity-a Possible Role In Facilita...mentioning
confidence: 99%
“…Its toxic effects include hallucinogenic action [5][6][7], which is dose-related, reason why the development of an efficient electroanalytical process is really actual. Moreover, being an indolic compound, substituted by donor groups, it is interesting as a monomer for a conducting polymer, analogous to those yet synthetized from other indoles [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%